Optimalisasi Lembaga Pembinaan Guru di Era Digital - Sintya Ramadayani; Tri Yolanda Putri; Vica Amalia (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research aims to find out how digital technology is used to optimize teacher development institutions in the digital era, what the implementation challenges are and what digital implementation steps are in optimizing digital development. The method used in this research is the library research method. Data collection by searching for sources from various sources such as books, journals and existing research. Data obtained from literature studies were analyzed using an interactive qualitative model. This data analysis model consists of data collection, data reduction, data presentation, and drawing conclusions. The research results show that there is optimization of teacher development institutions through teacher professional skills training in the digital era. The use of digital developments in optimizing teacher development institutions in educational institutions has the aim of forming teachers in implementing digital to help shape the character and professionalism of teachers. Challenges faced in integrating technology in teacher development institutions include the digital divide, attention to teacher training and development and data security and privacy. The steps for implementing technology are analyzing teacher coaching, digital-based learning planning, optimization, use of applications and supporting platforms, monitoring and evaluation as well as ongoing teacher training and development.